On the supramolecular properties of neutral, anionic and cationic cadmium complexes harvested from dithiolate–polyamine binary ligand systems. Issue 46 (11th November 2020) - Adhikari, Suman; Bhattacharjee, Tirtha; Das, Arijit; Roy, Subhadip; Daniliuc, Constantin Gabriel; Zaręba, Jan K.; Bauzá, Antonio; Frontera, Antonio
Abstract : Three Cd(ii ) complexes [Cd(i-mnt)(DMSO)2 ] n (1 ), {[Cd(i-mnt)pn]·2H2 O} (2 ), and [Cd(i-mnt)3 ][Cd(tren)2 ]2 (3 ) harvested from 1, 1-dicyanoethylene-2, 2-dithiolate (i-mnt 2− ) and polyamine ligand systems have been designed, synthesized and structurally characterized. Abstract : Three Cd(ii ) complexes [Cd(i-mnt)(DMSO)2 ] n (1 ), {[Cd(i-mnt)pn]·2H2 O} (2 ), and [Cd(i-mnt)3 ][Cd(tren)2 ]2 (3 ) harvested from 1, 1-dicyanoethylene-2, 2-dithiolate (i-mnt 2− ) and polyamine ligand systems have been designed, synthesized and structurally characterized. Single-crystal X-ray diffraction analysis reveals that these complexes exhibit diverse supramolecular architectures primarily thanks to different coordination modes adopted by (i-mnt 2− ) and polyamine ligands, and also owing to their disparate conformational flexibility. Indeed, polyamines (pn = 1, 2-diamino propane, tren = diethylenetriamine) and (i-mnt 2− ) ligands demonstrate the impact of the directing effect of the ligands' spatial extension, binding abilities and flexibility on the resulting structures of the complexes. Complex 1 is a 2D coordination polymer, whereas discrete complex 2 involves a cadmium center with a distorted octahedral geometry and forms a hydrogen bonding network of an unprecedented topological type ({4 11 6 9 8}{4 4 6 2 } point symbol notation). Complex 3 is a cocrystalline aggregate of one anionic [Cd(i-mnt)3 ] 4− unit flanked by two cationic [Cd(tren)2 ] 2+ units. DFT calculations (M06-2X/def2-TZVP level of theory) were performed in order to quantify the energetic contributions of non-covalent interactions. In 2, the energetics of hydrogen bonding interactions is explored while in the case of 3 unidirectional electrostatic interactions between the counterions are studied. Analyses of Hirshfeld surfaces (HSs) and of two-dimensional fingerprint plots provided another means of quantification of intermolecular contacts experienced by the neutral, cationic, and anionic cadmium complexes. It is found that the calculated contact contributions to the HS of neutral complex 2 are similar to the HS properties of cationic complexes in 3, i.e. being dominated predominantly by H⋯H and S⋯H contacts, despite significant differences in their structures. Moreover, the steady-state luminescence properties of dimethylsulfoxide solutions of the ligand (i-mnt 2− ) and of complexes 1–3 are also examined.